Efektivitas Konseling Kelompok Teknik Rational Emotive Imagery dan Homework Assigment untuk Meningkatkan Tanggung Jawab Remaja - Slamet Suryatmoko (Prosiding University Research Colloquium, 2021)
Because of the consequences of low youth responsibility in Menayu Hamlet, MenayuVillage, Muntilan, Magelang, this study was performed on the youth of Menayu Hamlet,Menayu Village, Muntilan, Magelang. The purpose of this study is to see whether groupcounseling using the Rational Emotive Imagery Technique and the Homework AssignmentTechnique can help youth in Menayu Hamlet, Menayu Village, Muntilan, Magelang getmore responsible.With a Randomized Pretest Posttest Comparison Group Design research design, this typeof study is a true experiment. The subjects in this research were 10 teens whose are dividedinto 2 groups: 5 teenagers in the Rational Emotive Imagery Technique group and 5teenagers in the Homework Assignment Technique group. Sample was executed using arandom sampling technique. With the help of SPSS 25, the data was analyzed using OneWay Anova parametric analysis. The therapy of group counseling services occurs over thecourse of nine meetings.The findings of this study show that group counseling using the Rational Emotive ImageryTechnique and the Homework Assignment Technique can help teenagers are becomingmore responsible. The study's findings were supported by the One Way Anova ParametricStatistics test, which returned a probability considerable value of 0.001. There is adifference in the average score of the responsibility questionnaire between the two classesafter testing the data. The experimental group 1 had a percentage increase of 10.26%,whereas the experimental group 2 have seen a percentage increase of 12.21%. This studyfound that group counseling using the Homework Assignment technique is more effectivethan group counseling using the Rational Emotive Imagery technique in improvingresponsibility.